AORTIC STIFFNESS IS INCREASED IN NORMOTENSIVE PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS. (June 2018) - Mule', G.; Morreale, M.; Savoja, A.L.; Pugliares, C.; Ferrante, A.; Cusimano, C.; Castiglia, A.; Cottone, S.
Abstract : Objective: Patients with systemic lupus erythematosus (SLE) have a 4- to 10-fold increased risk of developing cardiovascular (CV) events compared with the general population. The enhanced CV risk conferred by SLE may in part be mediated through preclinical CV damage. Large artery stiffness is usually assessed by measuring aortic pulse wave velocity (aPWV), a marker of early vascular aging (EVA) and an independent predictor of adverse CV prognosis. Several studies examined aortic stiffness in SLE with inconsistent results. The aim of our study was to evaluate aPWV and the prevalence of EVA in a group of normotensive patients with SLE and to compare these values with those obtained in age- and gender- matched control subjects. Design and method: Aortic PWV was measured by a validated oscillometric device (Arteriograph). EVA was identified when the age-adjusted z-score of aPWV exceeded +1.96 (EVA1). The aPWV z-score was calculated using the ratio "Observed PWV – Predicted PWV/SD Predicted", where the predicted PWV values were computed using a regression equation obtained from the healthy cohort of the European study of The Reference Values for Arterial Stiffness' Collaboration. We adopted also another definition of EVA (EVA2), wherein we included individuals with PWV values above the 90th percentile of aPWV distribution in the above mentioned population. Results: We enrolled 57 patients with SLE, aged 37.6 ± 11 years (9% men) and 29 healthy controls, aged 37.6 ± 9 years (10 % men). Aortic PWV, aPWV z score (see figure), as well as prevalence of EVA1 (12.3 vs 0 %; p = 0.049) and EVA2 (19.3 vs 0 %; p = 0.011) were significantly higher in SLE patients than in controls. The associations of aPWV and of aPWV z score with SLE were confirmed in multivariate models built in the overall study population, after adjustment for age, sex, BMI and mean blood pressure (both p < 0.001). Figure. No caption available. Conclusions: The impaired aortic distensibility we observed in patients with SLE may help to explain their increased CV risk.